2021
DOI: 10.30935/conmaths/11110
|View full text |Cite
|
Sign up to set email alerts
|

College of Education Pre-Service Teachers’ Attitude in Terms of Usefulness, Confidence and Enjoyment towards Geometry by Gender

Abstract: This study investigated gender differences in pre-service teachers' attitude towards geometry in Northern Region of Ghana. The research design was descriptive cross-sectional survey. A concurrent mixed-methods approach was adopted using both closed and open-ended questionnaire items. The population for the study was one thousand, six hundred and sixty-nine (1669) level 200 Pre-service Teachers (PSTs). The sample composed of two hundred and forty (240), comprising 120 PSTs each of female and male. The sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The results in the context of the study revealed that when participants perceived the use of tablet devices, they become interested in their work, had fun and enjoyed the work that they are doing, and as such, looked forward to doing their work with technology. These results are sustained by other studies in that, when teachers have positive attitudes towards the use of technological tools, their teaching becomes more enjoyable and interesting in the process (Salifu et al, 2021). In contrast, the results of this current study also indicated negative attitudes towards technology.…”
Section: Discussionsupporting
confidence: 80%
“…The results in the context of the study revealed that when participants perceived the use of tablet devices, they become interested in their work, had fun and enjoyed the work that they are doing, and as such, looked forward to doing their work with technology. These results are sustained by other studies in that, when teachers have positive attitudes towards the use of technological tools, their teaching becomes more enjoyable and interesting in the process (Salifu et al, 2021). In contrast, the results of this current study also indicated negative attitudes towards technology.…”
Section: Discussionsupporting
confidence: 80%
“…As a teacher and writer, Harun Reşit's examples from daily life for science concepts in his book "Yeni Eşya Dersleri", which was published in 1936 and taught in the 5th grade of primary schools (Tunç & Tuğluoğlu, 2013) support his advocacy of giving comprehensible examples from daily life. Although we assume that the example of Harun Reşit took place in the pre-Republican period and that teaching methods and policies have changed since then, research (Güler & Altun, 2015;Salifu et al, 2021;Yiğit-Koyunkaya et al, 2018) suggests the opposite. In other words, unfortunately, today's teachers also have difficulties in relating geometry teaching to daily life.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 98%
“…In the literature, this situation is caused by memorization of the properties of shapes, insufficient presentation of examples (Fujita & Jones, 2007); students' inability to use mathematical language, considering only prototypes of geometric shapes and having misconceptions about geometric concepts (Güler & Altun, 2018), thinking that geometry is not useful (Okur, 2006); the superficial handling of geometry topics in teacher training curricula, the fact that a geometry problem can be solved in more than one way (Melo & Martins, 2015). Among these reasons, the idea that geometry is useless is a common thought among students (Okur, 2006;Salifu et al, 2021;Ünlü, 2014). This idea also shows that students do not have a learning experience that will enable them to realize the importance of geometry in real life (Abdelfatah, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that Van Hiele's Phase-Based Instructional Strategy is superior to traditional instructional strategies in enhancing students' disposition toward geometry. Therefore, using Van Hiele's phase-based instructional technique can be seen as one of the effective strategies for improving students' attitudes toward geometry (Awofala et al, 2013;Karjanto, 2017;Ma & Kishor, 1997;Peker & Mirasyediolu, 2003;Recber et al, 2018;Salifu et al, 2021;Usman et al, 2019) Van Hiele's Phase-Based Instructional Strategy possesses strengths from both the students' and teachers' perspectives. The teaching technique employed a sequential approach, carefully organized in phases, inspiring students to learn geometry effectively.…”
Section: Van Hiele's Phase-based Instructional Strategymentioning
confidence: 99%